Ray Tracer Simulation of Si-Based Solar Cells using Al2O3/ITO as Double Layers Anti Reflective Coating - Hamdan, Nurul Aina Nabihah; Yusof, Noorsyam; Yusoff, Mohd Zaki Mohd (Trends in Sciences, 2023)
The solar cell has become one of the options for a greener world. Various studies have been done to achieve a solar cell with high efficiency and reasonable price. This study’s objective is to investigate how the thickness and base angle of the front layer affect the optical and electrical characteristics of Si-Based Solar cells. To accomplish this study, heterojunction solar cells using Al2O3/ITO as the double layer anti-reflection coating are analyzed using the Wafer Ray Tracer simulation by the PV Lighthouse. Al2O3 and ITO layers are used as a double anti-reflection coating (DLARC) in the light trapping strategy to support the reflection, absorption, and transmission (R, A and T) of the silicon solar cell. It acts to minimize reflectance and improves the overall efficiency of the solar cell. DLARC variation focuses on increasing absorption while decreasing reflection and transmission. The high refractive index of the hydrogenated a-Si (a-Si: H) emitter layer generates excessive reflection losses in SHJ solar cells making the silicon wafer have a low absorption efficiency. The DLARC thickness and base angle are varied as part of the simulation using the Wafer Ray Tracer by PV Lighthouse. The surface morphology of upright pyramid texture, height is 3.536 µm, texture base angle 54.74 °, and width 5 µm are used for reference scheme. Four schemes will be analyzed throughout this study along with the reference scheme. The result of this study is that Scheme 3 gives the optimum result with 99 % absorption, 21 % reflection and 67 % transmission. The goal of this study is to evaluate the impact of ARC thickness on optical and electrical characteristics. The best outcome is produced by varying the thickness and base angle of Scheme 3. The highest Jmax value, 0.3842 mA/cm2, is found in Scheme 3. HIGHLIGHTS The high refractive index of the hydrogenated a-Si (a-Si: H) emitter layer causes significant reflection losses in SHJ solar cells, resulting in a low absorption efficiency for the silicon wafer The double anti-reflection coating (DLARC) thickness and base angle are modified as part of the simulation using PV Lighthouse’s Wafer Ray Tracer The best results are obtained by adjusting the thickness and base angle of Scheme 3. Scheme 3 has the highest Jmax value of 0.3842 mA/cm2 GRAPHICAL ABSTRACT